PROSES BERPIKIR KREATIF SISWA DALAM PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI KEMAMPUAN MATEMATIKAPADA SISWA KELAS X MIA SMAN 6 SURAKARTA - Wulantina, Endah; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The research aims to describe the students’ creative thinking process of tenth grade of MIA of SMAN 6 Surakarta in solving mathematics problems towards students who have high, medium and low ability in mathematics. The researcher choosed qualitative research in case study design. The results showed that 1). Students’ creative thinking process in the tenth grade of MIA of SMAN 6 Surakarta with high ability in Mathematics are (a) Preparation, the students identify the prior knowledge about the assignment carefully than the students select the information in solving the problem appropriately; (b) Incubation, the students turn silent when they are thinking about how to solve the problem, the students memorize the way to solve the problem; (c) Illumination, the students continue the first idea which is found before; (d) Verification, the students recheck the problem solving before taking the conclusion, the students test the result by suiting to the data from the assignment. 2) The students’ creative thinking process in the tenth grade of MIA of SMAN 6 Surakarta with medium ability in Mathematics are (a) preparation, the students identify well the problem which is being asked select the information appropriately but they need some stimulus from another person; (b) Incubation, the students turn silent when they are thinking about how to solve the problem, the students memorized the way to solve the problem; (c) Illumination, the students only focus on the relevant information and could not explore the idea to find out the idea, here students also need the stimulus from another person; (d) verification, the students recheck the result before taking conclusion; 3) the students’ creative thinking process in the tenth grade of MIA of SMAN 6 Surakarta with low ability in Mathematics are: (a) Preparation, the students identify well the problem which is being asked, the students select the information recursively by comprehending the assignment. They also still need the stimulus in the form of question; (b) Incubation, the students memorize the appropriate pattern to solve the problem but sometimes they hesitate so they ask the problem to the researcher; (c) Illumination, the students solve the problem from what they already learnt from the previous way, the students focus on the relevant information and tent to avoid the complex information so that the student could not explore the idea to find out another idea, they tent to solve the problem with one idea; (d) Verification, the students recheck the result before taking conclusion but there are many corrections in the final answer.Keywords: Ability in Mathematics,  Creative Thinking Process, Mathematics Problem Solving.